1996
DOI: 10.1002/(sici)1097-0290(19960720)51:2<168::aid-bit6>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Pathway kinetics and metabolic control analysis of a high-yielding strain ofPenicillium chrysogenum during fed batch cultivations

Abstract: A kinetic model representing the pathway for the biosynthesis of penicillin by P. chrysogenum has been developed. The model is capable of describing the flux through the biosynthetic pathway, and model simulations correspond well with measurements of intermediates and end products. One feature of the present model structure is that it assumes the kinetics of the enzyme isopenicillin N synthetase (IPNS) to be first order with respect to the dissolved oxygen concentration in the range of 0.070 to 0.18 mM (25% to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…The expected mechanism behind the decrease in q p was the decreased rate of IPNS enzyme due to oxygen limitation [ 23 ], which was apparent from the measured metabolite levels, where the IPNS concentration decreased while the intracellular ACV accumulated, both of which were most affected by the lowest DO level. These observations are in contrast to the measurements of Henriksen et al., who reported increased IPN concentrations under low DO concentrations of 0.019–0.344 mmol L −1 [ 15 ]; however, previous findings of ACV accumulation in the intra‐ and extracellular space is consistent our observations [ 15 , 21 ]. Our results suggested that at DO concentrations between 0.013 and 0.025 mmol L −1 , the IPN levels decrease to values that approach or fall below the Km values of the IAT and IAH enzymes, which reduce penicillin production.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…The expected mechanism behind the decrease in q p was the decreased rate of IPNS enzyme due to oxygen limitation [ 23 ], which was apparent from the measured metabolite levels, where the IPNS concentration decreased while the intracellular ACV accumulated, both of which were most affected by the lowest DO level. These observations are in contrast to the measurements of Henriksen et al., who reported increased IPN concentrations under low DO concentrations of 0.019–0.344 mmol L −1 [ 15 ]; however, previous findings of ACV accumulation in the intra‐ and extracellular space is consistent our observations [ 15 , 21 ]. Our results suggested that at DO concentrations between 0.013 and 0.025 mmol L −1 , the IPN levels decrease to values that approach or fall below the Km values of the IAT and IAH enzymes, which reduce penicillin production.…”
Section: Discussioncontrasting
confidence: 71%
“…Bainbridge et al. reported a linear relationship between IPNS activity and the O 2 concentration within the range of 0.07 to 0.18 mmol L −1 [ 23 ], which was used in modeling studies [ 21 , 22 , 45 ]. However, at lower O 2 concentrations (<0.07 mmol L −1 ), the effect of DO on the rate of the IPNS enzyme has not yet been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation